Mass transfer in one-dimensional nanoporous crystals with different surface permeabilities - Heinke, Lars; Kärger, Jörg (Diffusion Fundamentals, 2008)
The use of optical techniques, such as interference microscopy and IR micro-imaging, has enabled the direct observation of transient concentration profiles. In a one-dimensional crystal, surface permeabilities on opposing crystal faces are usually equal, so that mass transfer occurs symmetrically and the fluxes through both crystal faces are identical. If the surface permeabilities on opposing crystal faces are different from each other, mass transfer is not symmetrical anymore. We are going to show that the fraction of molecular uptake (or release) through a given host face is inversely proportional to the time constant of uptake/release via this crystal face. This finding permits a straightforward estimate of the influence of asymmetry on overall uptake.